Glycolytic Enzyme PKM2 Mediates Autophagic Activation to Promote Cell Survival in NPM1-Mutated Leukemia - Wang, Lu (Int J Biol Sci, 2019)
Acute myeloid leukemia (AML) with mutated nucleophosmin (NPM1) has been defined as a distinct leukemia entity in the 2016 updated WHO classification of myeloid neoplasm. Our previous report showed that autophagic activity was elevated in NPM1-mutated AML, but the underlying molecular mechanisms remain elusive. Mount of study provides evidence that glycometabolic enzymes are implicated in the autophagic process. Pyruvate kinase isoenzyme M2 (PKM2), a key glycolytic enzyme, has been recently reported as a tumor supporter in leukemia. However, little is known about the roles of PKM2 in autophagic activity in NPM1-mutated AML. In this study, PKM2 highly expressed in NPM1-mutated AML, and partially, high levels of PKM2 were upregulated by PTBP1. Further experiments demonstrated that PKM2 mediated autophagic activation and increased the phosphorylation of key autophagy protein Beclin-1. Importantly, functional experiments demonstrated that PKM2 contributed to cell survival via autophagic activation. Ultimately, high PKM2 expression was associated with short overall and event-free survival time in NPM1-mutated AML patients. Our findings indicate for the first time that glycolytic enzyme PKM2 mediates autophagic activation and further contributes to cell survival in NPM1-mutated AML, suggesting that PKM2 may serve as a promising target for treatment of NPM1-mutated AML.